The relationship of organizational culture and employees performance at Universiti Teknologi MARA Terengganu / Khairunnisa Zainal Abidin - Zainal Abidin, Khairunnisa (2015)
The objective of this current research was to analyze dimension of organizational culture that affected the employees at Universiti Teknologi MARA Terengganu. The importance and contribution of this study was to provide researcher better understanding of factors that affect employee's performance in Universiti Teknologi MARA Terengganu. There were 443 employees who work in Universiti Teknologi MARA Terengganu, based on the Universiti Teknologi MARA Terengganu website. 201 questionnaires were spread cut and 105 questionnaires used to analyze the data in SPSS version 22. The result supports that, the organizational culture can affect the employee's performance and that were consistent with the previous explanation. Future research need to incorporate other variables that can affect the employee's performance.